Mobile Banking Service Quality and User Loyalty Using MSQUAL: A Systematic Literature Review - Nashikha, Ainun; Huda, Muhammad Qomarul; Fitroh, Fitroh; Durachman, Yusuf; Waspodo, Bayu (Sinkron : jurnal dan penelitian teknik informatika, 2025)
Digital transformation has made mobile banking a core service in the banking industry, emphasizing service quality as a critical factor for user satisfaction and loyalty. This study presents a systematic literature review (SLR) of mobile banking research from 2021 to 2025, guided by PRISMA and structured using the PICOC framework (Population, Intervention, Comparison, Outcome, Context) to systematically select and evaluate relevant studies. The MS-QUAL model, comprising nine dimensions: efficiency, system availability, responsiveness, privacy, content, contact, billing, fulfillment, and compensation, was used as the evaluation framework. Out of 924 initially identified articles, 20 met the inclusion criteria for in-depth analysis. Findings show that efficiency, system availability, privacy, responsiveness, content, and fulfillment consistently drive user satisfaction, while compensation, contact, and billing have limited influence. Satisfaction serves as the primary mediator connecting service quality to loyalty, indicating that improvements in MS-QUAL dimensions must translate into positive user experiences to foster long-term loyalty. The study further highlights challenges in maintaining security standards, adapting traditional dimensions to evolving user expectations, and ensuring consistent service quality. Opportunities lie in leveraging technologies such as AI, blockchain, and big data to create personalized, secure, and interactive experiences, enhancing both functional and emotional engagement. Overall, MS-QUAL remains a relevant and flexible framework for evaluating mobile banking service quality when aligned with contemporary technological advances and user-centered strategies.